Cohabiting and becoming a parent: Associations with changes in physical activity in the 1970 British cohort study - Werneck, André O. [UNESP]; Winpenny, Eleanor M.; Van Sluijs, Esther M. F.; Corder, Kirsten (Springer Nature, 2020)
Background: We examined the association between family-related life events (cohabitation/marriage and becoming a parent) and change in physical activity. Methods: Longitudinal data (n = 8045) from the 1970 British Cohort Study (30 and 34 years) were included. Life events (beginning cohabitation/marriage and becoming a parent) were reported and coded: 0 no, 1 yes, for each event occurring between 30 and 34 years. Participants reported frequency of participation in leisure-time physical activity at 30 and 34 years (Likert scale: mean change calculated ranging between - 4 and 4). Linear regression models were used to examine the association between life events and physical activity change (comparing individuals experiencing events between 30 and 34 years versus never experiencing the event - excluding participants that experienced previous events - with a final analysis sample of n = 3833 in parenthood analysis; n = 1137 in cohabitation analysis). Interaction terms were used to analyse combined parenthood and cohabitation status. Analyses were adjusted for level of education achieved, ethnicity, country of origin and other life events. ANCOVA was used to examine associations between change in physical activity and child age. Results: Compared to remaining without children, becoming a parent was associated with a greater reduction in physical activity among men [β:-0.234(95%CI:-0.396 to - 0.072)] but not women [0.126(- 0.048;0.301)]. No associations were found between cohabitation and physical activity. Men who became fathers both while cohabitating [- 0.201(- 0.383;-0.020)] and without cohabiting [- 0.937(- 1.623;-0.250)] experienced greater physical activity declines than those remaining single and without children; the decline was greatest among non-cohabiting fathers. These associations did not differ by child age. Conclusions: Parenthood appears to differentially impact physical activity for men and women; this association also differs by cohabitation status. Parenthood appears to be most detrimental to physical activity levels among men. Interventions for physical activity could target new or soon-to-be parents, especially fathers. Further analyses with device-measured physical activity data would be valuable to advance understanding of these associations.
Keywords: Adult; Child; Exercise; Family; Father; Mother; Parent